Experimental Study of Tissue-type Plasminogen Activator Gene to Prevent Vein Grafts Stenosis - 蒋雄刚 刘小斌 张凯伦 夏家红 向道康 吴龙 周诚 (Journal of Huazhong University of Science and Technology. Medical sciences, 2006)
The effects of in vivo local expression of recombined human tissue-type plasminogen activator （t-PA） gene on the thrombosis and neointima formation of vein grafts were explored. Jugular vein-to-artery bypass grafting was performed on 72 New Zealand white rabbits. The rabbits were divided into 3 groups according to the different processing methods： transfected t-PA gene group （n = 24）, vector group （n= 24） and blank control group （n = 24）. Samples of vein grafts were harvested at different time points after surgery. The expression of t-PA gene in vein graft was detected by RT-PCR and the synthesis of t-PA protein by Western-Blot assay. The t-PA activity was measured by chromogenic substrate assay. The Cr51 labeled platelets accumulation in vein grafts was counted. The histopathological changes were compared in intima hyperplasia index among the three groups after operation. The results showed that at the 2^nd , 5^th , 14^th and 28^th day after operation, RT-PCR and Western-blot confirmed the expression of t-PA mRNA and protein at the site of gene transfer. The t-PA activity detected on the 2^nd, 5^th, 14^th and 28^th day in experimental group was 370. 63±59. 44, 344. 13±48. 47, 252.87±51.80 and 161.75±68. 94 U/g respectively, and disappeared on the 60^th day and undetected in the control groups. The number of platelets accumulated in the vein grafts in gene group, vector group and blank control group was （85. 04 ± 21.58） 10s, （225.87±85.13） 10^6 and （211.57±78.02） 10^6 respectively. The number of platelets accumulated in gene group was significantly fewer than that in the control groups. Morphometric analysis revealed that intimal hyperplasia was markedly reduced in the t-PA gene group as compared with that in the control groups. It was suggested that the local expression of t-PA gene in vein graft significantly inhibited the accumulation of platelets, thrombosis and concomitant intimal hyperplasia, by which stenosis of bypass graft could be prevented effectively.